1999
DOI: 10.1104/pp.121.4.1127
|View full text |Cite
|
Sign up to set email alerts
|

Stop-and-Go Movements of Plant Golgi Stacks Are Mediated by the Acto-Myosin System

Abstract: The Golgi apparatus in plant cells consists of a large number of independent Golgi stack/trans-Golgi network/Golgi matrix units that appear to be randomly distributed throughout the cytoplasm. To study the dynamic behavior of these Golgi units in living plant cells, we have cloned a cDNA from soybean (Glycine max), GmMan1, encoding the resident Golgi protein ␣-1,2 mannosidase I. The predicted protein of approximately 65 kD shows similarity of general structure and sequence (45% identity) to class I animal and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

38
545
4
5

Year Published

2001
2001
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 528 publications
(592 citation statements)
references
References 50 publications
(59 reference statements)
38
545
4
5
Order By: Relevance
“…the cell periphery (Nebenführ et al, 1999). Co-expression of FT SL24 mRNA with Golgi 257 marker Man49-mCherry, the first 49 amino acids of α-1,2 mammosidase I 258 (Saint-Jore- Dupas et al, 2006), revealed that the transport of Golgi and FT SL24 mRNA 259 was mediated along the same transvacuolar strands (Fig.…”
Section: Movie 1) Previous Results Show That Golgi Is Transported Thmentioning
confidence: 99%
“…the cell periphery (Nebenführ et al, 1999). Co-expression of FT SL24 mRNA with Golgi 257 marker Man49-mCherry, the first 49 amino acids of α-1,2 mammosidase I 258 (Saint-Jore- Dupas et al, 2006), revealed that the transport of Golgi and FT SL24 mRNA 259 was mediated along the same transvacuolar strands (Fig.…”
Section: Movie 1) Previous Results Show That Golgi Is Transported Thmentioning
confidence: 99%
“…The involvement of myosin motors has, in most cases, been presented as a major possibility rather than a proven fact (Olyslaegers and Verbelen, 1998;Kandasamy and Meagher, 1999). The well-analyzed movement of Golgi units in plants has relied on the use of two drugs, NEM and BDM, for associating myosin motors with Golgi motility (Boevink et al, 1998;Nebenfü hr et al, 1999). Thus, Boevink et al (1998) (2000) demonstrated that treatment of Chinese hamster ovary cells with up to 10 mm BDM had no effect on peroxisomal movement.…”
Section: Peroxisome Movement May Not Involve Myosin Motors and Be Anmentioning
confidence: 99%
“…Following published literature (Nebenfü hr et al, 1999;Huber et al, 2000;Samaj et al, 2000), BDM was used at five different concentrations (2.5, 5, 10, 20, and 30 mm) but failed to arrest peroxisomal movement completely (Fig. 10).…”
Section: Effect Of the Myosin Inhibitors On Peroxisome Movementmentioning
confidence: 99%
See 2 more Smart Citations